Data base of Acute changes in metabolic and cardiovascular variables resulting from sedentary behavior exposure: a systematic review - Gomes da Silva, Jonas Ribeiro (2026)
PURPOSE: This review aimed to analyze possible acute effects resulting from prolonged exposure to sedentary behavior on metabolic and cardiovascular variables. METHODOLOGY: Following the PRISMA guidelines, a systematic search was conducted in the PubMed, Embase, and Virtual Health Library databases between March 4 and April 16, 2024, identifying 21 experimental studies for the final qualitative synthesis. RESULTS: The main outcome variables reported were the area under the glucose and insulin curve, blood pressure, blood flow, and flow-mediated dilation. Regarding metabolic variables, reductions in glucose and insulin concentrations and increases in triglycerides while sitting were observed over time. For cardiovascular variables, the studies analyzing blood pressure showed conflicting results; however, endothelial variables showed deleterious changes during prolonged sitting. CONCLUSION: The studies included focused mainly on strategies to mitigate the harmful effects of sedentary behavior, highlighting a lack of research specifically aimed at addressing real-time effects during uninterrupted sedentary sessions. Therefore, standardized approaches and dose–response analyses are essential to enhance understanding of the impacts of prolonged sedentary behavior on health and metabolism.